We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
180
2
avatar

The asymptotes of a hyperbola are y=x+1 and y=3-x. Also, the hyperbola passes through (3,3). Find the distance between the foci of the hyperbola.

 Mar 27, 2019
 #1
avatar+10778 
0

The asymptotes of a hyperbola are y=x+1 and y=3-x. Also, the hyperbola passes through (3,3). Find the distance between the foci of the hyperbola.

laugh

 Mar 27, 2019
edited by Omi67  Mar 27, 2019
 #2
avatar+23521 
+1

The asymptotes of a hyperbola are y=x+1 and y=3-x. Also, the hyperbola passes through (3,3).
Find the distance between the foci of the hyperbola.

 

Formula hyperbola:

\(\begin{array}{|l|rcll|} \hline 1. \text{ asymptote} & x+1 &=& y \\ & x+1-y &=& 0 \\\\ \hline 2. \text{ asymptote} & 3-x &=& y \\ & 3-x-y &=& 0 \\\\ \hline \text{hyperbola: } & (x+1-y)(3-x-y) + c &=& 0 \\\\ P(x=3,y=3) & (3+1-3)(3-3-3)+c &=& 0 \\ & (1)(-3)+c &=& 0 \\ & c &=& 3 \\ \text{hyperbola: } &\mathbf{ (x+1-y)(3-x-y) + 3} &\mathbf{=}& \mathbf{0} \\\\ & (x+1-y)(3-x-y) + 3 & = & 0 \\ & \Big((x-y)+1\Big)\Big(3-(x+y)\Big) + 3 & = & 0 \\ & 3(x-y)-(x-y)(x+y)+3-(x+y) + 3 & = & 0 \\ & 3(x-y)-(x-y)(x+y)+3-(x+y) + 3 & = & 0 \\ & 3x-3y-(x^2-y^2)+3-x-y + 3 & = & 0 \\ & 2x-4y-x^2+y^2+6 &=& 0 \quad | \quad \cdot (-1) \\ & x^2-2x -y^2+4y -6 &=& 0 \\ & x^2-2x -y^2+4y &=& 6 \\ & (x-1)^2-1 -(y-2)^2+4 &=& 6 \\ & (x-1)^2 -(y-2)^2 &=& 3 \quad | \quad :3 \\ & \dfrac{(x-1)^2}{3} - \dfrac{(y-2)^2}{3} &=& 1 \\ & \boxed{\text{Formula hyperbola:} \dfrac{ (x-h)^2 }{a^2}- \dfrac{ (x-k)^2 }{b^2} = 1 } \\ & a^2 = 3 \\ & a= \sqrt{3} \\\\ & b^2 = 3 \\ & b= \sqrt{3} \\ \hline \end{array}\)

 

\(\begin{array}{|l|rcll|} \hline \text{Focus}_1: & F_1(h+ae,k) \\ \text{Focus}_2: & F_2(h-ae,k) \\ \hline \text{Foci distance}: & && h+ae-(h-ae) \\ & &=&h+ae-h+ae \\ & &=& 2ae \quad | \quad e=\dfrac{\sqrt{a^2+b^2}}{a} \\ & &=& 2a\dfrac{\sqrt{a^2+b^2}}{a} \\ & &=& 2 \sqrt{a^2+b^2} \quad | \quad a^2=b^2= 3 \\ & &=& 2 \sqrt{3+3} \\ & &\mathbf{=}& 2 \mathbf{ \sqrt{6} } \\ \hline \end{array}\)

 

The distance between the foci of the hyperbola is \(\mathbf{2\sqrt{6} }\)

 

 

laugh

 Mar 27, 2019
edited by heureka  Mar 27, 2019

32 Online Users

avatar